Management of patients with metastatic teratoma with malignant somatic transformation. Issue 5 (September 2018) - Speir, Ryan; Cary, Clint; Foster, Richard S.; Masterson, Timothy A.
Abstract : Purpose of review: The purpose of this review is to examine the historical context alongside contemporary studies in order to provide the most current recommendations for the management of patients with metastatic teratoma with malignant somatic transformation (MST). Recent findings: The main themes in the recent literature covered herein include prognostic features, the management of early-stage disease, recommended chemotherapeutic and surgical strategies as well as recognized patterns of late relapse. Summary: Recent literature, combined with a significant contribution from historical studies, suggests that while MST is uncommon, its aggressive nature coupled with its resistance with traditional germ cell tumor chemotherapies makes it very difficult to manage. The key message is that surgery is recommended in all resectable MST from primary retroperitoneal lymph node dissection for clinical stage I, to radical removal of disease after chemotherapy and when chemotherapy fails. In advanced cases with documented spread of the transformed histologic subtype, systemic therapies targeted to the identified tumor type should be considered.